A prospective, cohort evaluation of major and minor airway management complications during routine anaesthetic care at an academic medical centre. (26th September 2016) - Huitink, J. M.; Lie, P. P.; Heideman, I.; Jansma, E. P.; Greif, R.; van Schagen, N.; Schauer, A.
Summary: The aim of this study was to develop an audit tool to identify prospectively all peri‐operative adverse events during airway management in a cost‐effective and reproducible way. All patients at VU University Medical Center who required general anaesthesia for elective and emergency surgical procedures were included during a period of 8 weeks. Daily questionnaires and interviews were taken from anaesthesia trainees and anaesthetic department staff members. A total of 2803 patients underwent general anaesthesia, 1384 men and 1419 women, including 2232 elective patients and 571 emergency procedures, 697 paediatric and 2106 adult surgical procedures. A total of 168 airway‐related events were reported. The incidence of severe airway management‐related events was 24/2803 (0.86%). There were 12 (0.42%) unanticipated ICU admissions, two patients (0.07%) required a surgical airway. There was one (0.04%) death, one cannot intubate cannot oxygenate (0.04%), one aspiration (0.04%) and eight (0.29%) severe desaturations < Sp O2 50%. We suggest that our method to determine and investigate airway management‐related adverse events could be adopted by other hospitals.